First Detection and Genomic Characterization of Linezolid-Resistant Enterococcus faecalis Clinical Isolates in Bulgaria - Tanya V. Strateva; Preslava Hristova; Temenuga J. Stoeva; Hristina Hitkova; Slavil Peykov (Microorganisms)
Linezolid is an oxazolidinone antibiotic and is considered a last-resort treatment option for serious infections caused by problematic Gram-positive pathogens, including vancomycin-resistant enterococci. The present study aimed to explore the linezolid resistance mechanisms and genomic characteristics of two vancomycin-susceptible Enterococcus faecalis isolates from Bulgaria. The strains designated Efs2503-bg (inpatient from Pleven) and Efs966-bg (outpatient from Varna) were recovered from wounds in 2018 and 2023, respectively. Antimicrobial susceptibility testing, whole-genome sequencing, multilocus sequence typing, and phylogenomic analysis based on 332 linezolid-resistant E. faecalis genomes were performed. Efs2503-bg was high-level resistant to linezolid (MIC > 256 mg/L) and displayed the G2576T mutation affecting three of the four 23S rDNA loci. Efs966-bg (MIC = 8 mg/L) carried a plasmid-located optrA determinant surrounded by fexA and ermA. No mutations in the genes encoding for ribosomal proteins L3, L4, and L22 were detected. The isolates belonged to the sequence types ST6 (Efs2503-bg) and ST1102 (Efs966-bg). Phylogenomic analysis revealed that Efs2503-bg and Efs966-bg are genetically distinct, with a difference of 12,051 single-nucleotide polymorphisms. To our knowledge, this is the first report of linezolid-resistant enterococci in Bulgaria. Although the global incidence of linezolid-resistant enterococci is still low, their emergence is alarming and poses a growing clinical threat to public health.